(untitled) - Devine, Jack (New York, 2014)
A master class in spycraft from one of its greatest practitioners. Jack Devine is one of the legendary spymasters of our time. He was in Chile when Allende fell; he ran Charlie Wilson's war in Afghanistan; he had too much to do with Iran-Contra for his own taste, though he tried to stop it; he caught Pablo Escobar in Colombia; he tried to warn George Tenet that there was a bullet coming from Iraq with his name on it. Devine served America's interests for more than thirty years in a wide range of covert operations, ultimately overseeing the Directorate of Operations, a CIA division that watches over thousands of American covert operatives worldwide. Good Hunting is his guide to the art of spycraft, told with great wit, candor, and commonsense wisdom. Caricatured by Hollywood, lionized by the right, and pilloried by the left, the CIA remains one of the least understood instruments of the United States government. Devine knows more than almost anyone about the CIA's vital importance as a tool of American statecraft. Now, as he sees it, the agency is trapped within a larger bureaucracy, losing swaths of turf to the military and, most ominous of all, being transformed into a paramilitary organization. Its capacity to do what it does best has been seriously degraded. In wonderfully readable prose, Good Hunting aims to set the record straight. This is a revelatory inside look at an organization whose history has not been given its real due
Keywords: Cơ quan tình báo trung ương Hoa Kỳ.,United States. Central Intelligence Agency; Quan chức và nhân viên,Tiểu sử,Officials and employees,Biography